The Science of Spirit: Parapsychology, Enlightenment and Evolution by Luis Portela - Ginsberg, Robert (Journal of Scientific Exploration, 2022)
When one sees an opening chapter entitled “From Science to Love” it begs for further reading. After all, for most these are incongruent terms that represent two seemingly opposite sides in a debate, logic, and systematic evaluation vs. emotion. There have been many books written about the convergence of science and spirituality, and one cannot help but notice how some of today’s physicists are sounding more like spiritualists than scientists, but Dr. Portola uses this platform as wake up call for humanity. There is a brief discussion about some well-known enlightened beings in our history, including founders of today’s organized religions, and our progression from animism to polytheism, and eventually monotheism, but Portola astutely points out the role that science played in explaining natural phenomena. Our ancestors could not have imagined these discoveries, and it was science that moved us past idol worship to spiritual independence. The author is well versed in the primary disciplines of research that suggest survival and devotes part of the book to discussions of the nature of consciousness, neuroscience, thought transmission, psychokinesis, near-death experiences, reincarnation, mediumship, and instrumental TransCommunication, but the overall message is clear that science can show us the road but changing the world paradigm starts with individual transformation. In the discussion of the neurosciences and parapsychology it is suggested that perhaps an adjustment to the scientific method is indicated by putting more value on the anecdotal personal experiences that are so prevalent. In his discussion about a paradigm shift Portola suggests that all people, including scientists and mediums, will understand more by first finding themselves through contemplation and reflection. It is only after we open to the subtle layers of consciousness that we can achieve the necessary balance needed to reach our objectives. The suggestion that scientists also need to contemplate and reflect upon the bigger picture seems contrary to the definition of science, but I suspect that Portola is correct.